EFEKTIVITAS AKUN INSTAGRAM @SOSMEDMAKASSAR DALAM PEMENUHAN KEBUTUHAN INFORMASI KOTA MAKASSAR PADA MAHASISWA JURNALISTIK UIN ALAUDDIN MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This study aims to determine the effectiveness of Instagram social media @sosmedmakassar as a medium for disseminating information about Makassar City. The type of research used is a quantitative approach and descriptive type. While the objects in this study were Journalistic students at UIN Alauddin Makassar class of 2018, 2019, and 2020 as many as 145 people also became followers of the Instagram account @sosmedmakassar as respondents were selected by simple random sampling technique. The theory used is the theory of Effectiveness, Maslow's Hierarchical Needs theory from Maslow and the Information Needs theory used to analyze the results of the research.Data collection was carried out through online questionnaire distribution techniques. Data analysis techniques use measurement aids with a Likert scale and use simple linear formulas, validity tests, reliability tests, and t-tests. The results of the analysis are presented in the form of numbers which are then explained and interpreted in a description.The results of this study indicate that the Instagram account @sosmedmakassar is effective in fulfilling the information needs of Makassar City for UIN Alauddin Makassar Journalism students. This can be seen from the results of tests carried out by means of the multiple correlation test, the results show that the R values ​​(Correlation Coefficient) are 0.94 (effectiveness), 0.90 (caption)), and 0.119 (attention), because the R values ​​are at 0.80 – 1.000, variable X has a very strong relationship with variable Y. In addition to testing the hypothesis, hypothesis testing is done by means of the T-test using the paired sample t-test formula. The results show that t count > t table = 1,725 ​​> 1,655 (effectiveness), 2,581 > 1,655 (caption), and 1,776 > 1,655 (attention), so H0 is rejected and H1 is accepted, where H1 is the Instagram account @sosmedmakassar effective in fulfilling information needs Makassar City to journalistic students at UIN Alauddin Makassar.The researcher hopes that further research will be able to expand the scope of the research area so that it can represent the actual situation because the research was only conducted at UIN Alauddin Makassar journalistic students.